Penguatan Demokratisasi Pada Implementasi Program Nasional Pemberdayaan Masyarakat di Kelurahan Lakessi Kecamatan Maritengngae Kabupaten Sidrap - Sakaruddin Mandjarreki (Jurnal Berita Sosial, 2023)
Improving the quality of life of the community is the main goal of the nation’s ideology, which is a manifestation of a prosperous life. The main focus of efforts to improve this quality of life lies with the poor and other vulnerable groups whose numbers continue to increase. The government has designed policies to reduce the number of poor people through various community empowerment programs. These community empowerment programs give citizens the authority to plan development independently, based on the principles of democracy or community democratization. Community democratization is not just a concept, it has also become mainstream in alternative development discourse. Alternative development plans combine top-down and bottom-up planning paradigms. This research uses a qualitative approach with phenomenological methods. Research informants were selected using purposive sampling method, and data sources involved interviews and relevant references as primary and secondary data. Data analysis was conducted using the methods of reduction, presentation, and conclusion. The results show that community democratization, which includes equal participation opportunities, transparency in decision-making, inclusive and representative election of leaders, recognition of human rights, strengthening community capacity, and social and economic justice, is adequately addressed, although with varying levels of performance in all key aspects of community democratization.